2002
DOI: 10.1086/338569
|View full text |Cite
|
Sign up to set email alerts
|

Evidence forChlamydia trachomatisas a Human Papillomavirus Cofactor in the Etiology of Invasive Cervical Cancer in Brazil and the Philippines

Abstract: Chlamydia trachomatis infection was examined as a cause of invasive cervical cancer (ICC) among women with human papillomavirus (HPV) infection. In total, 499 women with incident ICC (ICC patients) and 539 control patients from São Paulo, Brazil, and Manila, the Philippines, were included. C. trachomatis antibodies were detected by microimmunofluorescence assay. Presence of HPV DNA in cervical specimens was determined by a polymerase chain reaction-based assay. C. trachomatis seropositivity was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
2
11

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(123 citation statements)
references
References 23 publications
2
108
2
11
Order By: Relevance
“…Our finding suggests a plausible mechanism whereby C. trachomatis infection could be associated with increased risk for cervical cancer, as has been reported in several epidemiological studies. 7,[10][11][12]23,24 It has been reported that C. trachomatis infection may induce large local amounts of pro-inflammatory chemokines, including IL-1, IL-8 and granulocyte-macrophage colony-stimulating factor 25 producing a chronic inflammatory background that may conceivably contribute to HPV DNA persistence in the cervix.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding suggests a plausible mechanism whereby C. trachomatis infection could be associated with increased risk for cervical cancer, as has been reported in several epidemiological studies. 7,[10][11][12]23,24 It has been reported that C. trachomatis infection may induce large local amounts of pro-inflammatory chemokines, including IL-1, IL-8 and granulocyte-macrophage colony-stimulating factor 25 producing a chronic inflammatory background that may conceivably contribute to HPV DNA persistence in the cervix.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have linked sexually transmitted infections (STIs) other than HPV with cervical cancer. 25 Herpes simplex type 2, 26 Chlamydia trachomatis 27,28 and Neisseria gonorrhoea 29 have all been associated with an increased risk for cervical intraepithelial neoplasia (CIN) and invasive cervical cancer, after accounting for infection with high-risk types of HPV. These infections excite chronic inflammatory response which causes the generation of free radicals, which are thought to play an important role in the generation and progression of cancers.…”
Section: Biological Factorsmentioning
confidence: 99%
“…It has been shown that there may be a role for infection as a co-factor in carcinogenesis e.g. inflammation, probably due to Chlamydia, may contribute to of cervical cancer [14]. Recently, demonstration of an exaggerated response to inflammation due to polymorphisms of IL6 and TNF alpha has been noted in some HNSCC patients that may result in a carcinogenic effect at a site of inflammation [15].…”
Section: Minor Risk Factorsmentioning
confidence: 99%